FRI0230 Retention rates of tnf inhibitors and abatacept used as a first biologic dmard in the treatment of rheumatoid arthritis: 8 years of experience from the rhumadata® registry. (15th June 2017) - Choquette, D; Bessette, L; Alemao, E; Haraoui, B; Massicotte, F; Mtibaa, M; Muratti, E; Pelletier, J-P; Postema, R; Raynauld, J-P; Rémillard, M-A; Sauvageau, D; et al.
Abstract : Background: Sustainability of treatment is important to consider when selecting a therapy for chronic conditions such as RA. Sustainability is a useful clinical marker for both long-term efficacy and safety. A recently published randomized controlled trial has demonstrated similar efficacy and safety profiles between abatacept (ABA) and adalimumab over 2 years. 1, 2 Objectives: To assess the long-term sustainability of ABA and anti-TNFs following treatment failure with a conventional synthetic DMARD (csDMARD) in comparable cohorts of patients (pts) with RA. Methods: Data from pts with RA seen at two tertiary centres and prescribed either ABA or a TNF inhibitor (adalimumab, certolizumab, etanercept, golimumab or infliximab) as their first biologic (b)DMARD after 1 January 2006 were extracted from the RHUMADATA® registry. The choice of therapy was a joint decision between the pt and the treating physician. Pts were followed until either they discontinued treatment, were lost to follow-up or the cut-off date of 9 January 2017. Pt baseline characteristics were compared using descriptive statistics and the cumulative incidence of biologic agent discontinuation using Kaplan-Meier methods. Overall differences in the discontinuation rates of biologic agents were tested using the log-rank test. Results: Overall, 641 pts met study criteria; 82 pts received ABA and 559 TNF inhibitors (adalimumab=136, certolizumab=52, etanercept=226, golimumab=88 and infliximab=57) as first-line treatment following inadequate response to csDMARDs. No clinically significant differences in baseline characteristics were noted between treatment groups. Most pts were diagnosed after January 2000 (72.5%) and were women (77.5%). Average age at diagnosis was 47.1 (SD=13.4) years, with a mean disease duration of 7.2 (7.8) years, and a mean CDAI of 43.1 (32.5) at baseline. No significant differences in retention rates were observed in the ABA and anti-TNF groups (Table, Figure). On average, pts treated with anti-TNFs and ABA maintained their treatment for 1.59 (1.91) and 1.90 (2.08) years, respectively. Lack of efficacy (47.6%) and adverse effects (22.0%) were the most commonly cited reasons for treatment discontinuation. Conclusions: Abatacept and TNF inhibitors demonstrate similar sustainability at 8-year, supporting studies 1, 2 that demonstrate that abatacept used after csDMARDs inadequate response is as safe and effective as a TNF targeting agents in the long term. References: Schiff M, et al. Ann Rheum Dis 2014;73:86–94. Schiff M, et al. Ann Rheum Dis 2008;67:1096–1103. Disclosure of Interest: D. Choquette Consultant for: BMS, Speakers bureau: BMS, L. Bessette Grant/research support from: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Consultant for: BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Celgene, Lilly, Novartis, E. Alemao Shareholder of: BMS, Employee of: BMS, B. Haraoui Grant/research support from: BMS, Janssen, Roche, Consultant for: Abbvie, Amgen, BMS, Celgene, Janssen, Merck, Pfizer, Roche, Sandoz, UCB, Speakers bureau: Pfizer, UCB, F. Massicotte: None declared, M. Mtibaa Shareholder of: BMS, Employee of: BMS, E. Muratti Employee of: BMS, J.-P. Pelletier: None declared, R. Postema Shareholder of: BMS, Employee of: BMS, J.-P. Raynauld Speakers bureau: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, Sanofi, Novartis, UCB, M.-A. Rémillard: None declared, D. Sauvageau: None declared, A. Turcotte Consultant for: Amgen, Abbvie, BMS, Celegene, Janssen, Roche, Pfizer, Lilly, Novartis, Merck, Sanofi, UCB, Speakers bureau: Amgen, Abbvie, BMS, Celegene, Janssen, Roche, Pfizer, Lilly, Novartis, Merck, Έ. Villeneuve Consultant for: Celgene, Cimzia, Pfizer, Speakers bureau: Abbvie, Roche, BMS, L. Coupal: None declared